2008
DOI: 10.1055/s-0028-1088374
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Activity of Oleanolic Acid by Inhibition of Secretory Phospholipase A2

Abstract: Oleanolic acid, a triterpenoid known for its anti-inflammatory properties, is commonly present in several medicinal plants. The present study evaluated the effect of oleanolic acid on sPLA (2), a key enzyme in inflammatory reactions. Oleanolic acid inhibited sPLA (2) activities of human synovial fluid (HSF), human pleural fluid (HPF) and VIPERA RUSSELLI (VRV-PL-V) and NAJA NAJA (NN-PL-I) snake venoms in a concentration-dependent manner. The IC (50) values of sPLA (2) from these sources ranged from 3.08 to 7.78… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 21 publications
(25 reference statements)
2
43
0
2
Order By: Relevance
“…Indeed, OA has been shown to inhibit the hyperpermeability and leukocyte migration from blood vessels into tissues [22,23] which occur in the first phase of inflammation. It is also known to inhibit the activity of phospholipase A [20], the membrane-bound enzyme responsible for releasing arachidonic acid from membranebound phospholipids. The current study showed that both derivatives of OA suppressed the early and later phases of albumin-and serotonin-induced inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, OA has been shown to inhibit the hyperpermeability and leukocyte migration from blood vessels into tissues [22,23] which occur in the first phase of inflammation. It is also known to inhibit the activity of phospholipase A [20], the membrane-bound enzyme responsible for releasing arachidonic acid from membranebound phospholipids. The current study showed that both derivatives of OA suppressed the early and later phases of albumin-and serotonin-induced inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…OA and its two semisynthetic derivatives inhibited both the early and late phases of albumin-/serotonin-induced inflammation. Indeed, steroid-like compounds have been shown to inhibited both the early and later phases of inflammation [20]. In his review on the pharmacological properties of oleanolic acid, Liu, 1995 [21] discussed the inhibitory effects of oleanolic acid on histamine and serotonin secretion during inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Oleanolic acid는 pentacyclic triterpene으로 유리산이나 triterpenoid saponin의 아글리콘 형태로 자연계에 흔히 존 재하면서 3) , 항산화 11,12) , 염증반응 억제 13) , 간 보호 14) , 위 보 호 15) , 암세포에 대한 독성 16) , 항 궤양 17) , 항고지혈증 18) 등 에 대한 생리활성을 가지고 있다 [19][20][21] . , 특히 정향 잎(Syzygium aromaticum; 1.65 g/100 g 건조중량) 24) , 올리브 잎(Olea europaea; 3.1 g/100 g 건조중량) [25][26][27] , 로즈마리 잎(Rosmarinus officinalis; 1.23/100 g 건조중량) [28][29][30] 등에서 추출 된다.…”
Section: Oleanolic Acidunclassified
“…1) is a pentacyclic triterpene widespread in the plant kingdom in the form of free acid or aglycone for triterpenoid saponins [27]. It is reported to possess interesting bioactivities including anti-inXammatory [10], hepatoprotective [23], antitumor [21], antiviral [29], and antimicrobial activities [19]. Previous studies from our laboratory and others have shown that oleanolic acid and its derivatives display antibacterial activity against oral pathogens [8,31,34].…”
Section: Introductionmentioning
confidence: 95%